N-Acetylcysteine Enhances the Recovery of Ischemic Limb in Type-2 Diabetic Mice - Qiang Zhu; Xuanyou Liu; Qingyi Zhu; Zehao Liu; Chunlin Yang; Hao Wu; Linfang Zhang; Xiujuan Xia; Meifang Wang; Hong Hao; Yuqi Cui; Guangsen Zhang; et al. (MDPI AG, 2022)
Critical limb ischemia (CLI) is a severe complication of diabetes mellitus that occurs without effective therapy. Excessive reactive oxygen species (ROS) production and oxidative stress play critical roles in the development of diabetic cardiovascular complications. N-acetylcysteine (NAC) reduces ischemia-induced ROS production. The present study aimed to investigate the effect of NAC on the recovery of ischemic limb in an experimental model of type-2 diabetes. TALLYHO/JngJ diabetic and SWR/J non-diabetic mice were used for developing a CLI model. For NAC treatment, mice received NAC (1 mg/mL) in their drinking water for 24 h before initiating CLI, and continuously for the duration of the experiment. Blood flow, mechanical function, histology, expression of antioxidant enzymes including superoxide dismutase (SOD)-1, SOD-3, glutathione peroxidase (Gpx)-1, catalase, and phosphorylated insulin receptor substrate (IRS)-1, Akt, and eNOS in ischemic limb were evaluated in vivo or ex vivo. Body weight, blood glucose, plasma advanced glycation end-products (AGEs), plasma insulin, insulin resistance index, and plasma TNF-a were also evaluated during the experiment. NAC treatment effectively attenuated ROS production with preserved expressions of SOD-1, Gpx-1, catalase, phosphorylated Akt, and eNOS, and enhanced the recovery of blood flow and function of the diabetic ischemic limb. NAC treatment also significantly decreased the levels of phosphorylated IRS-1 (Ser307) expression and plasma TNF-α in diabetic mice without significant changes in blood glucose and AGEs levels. In conclusion, NAC treatment enhanced the recovery of blood flow and mechanical function in ischemic limbs in T2D mice in association with improved tissue redox/inflammatory status and insulin resistance.